Eight forms of abuse: The validation and reliability of two multidimensional instruments of intimate partner violence - Vasiliauskaitė, Zuzana; Geffner, Robert (Psichologija, 2021)
Many researchers are still relying on older and more rigid instruments focusing mostly on the physical aspect of intimate partner violence (IPV). This way multidimensionality of IPV and complex experiences of IPV survivors’ are overlooked by many researchers, practitioners and decision-makers. Therefore, our study aimed to adopt to Lithuanian two multidimensional scales: the Composite Abuse Scale (CAS) and the Scale of Economic Abuse (SEA). As well as confirm its validity and reliability for the use for determining the experiences of Lithuanian women in intimate partner relationships. Through various channels 311 women, survivors of IPV were recruited. The structure of both measurements was validated using Confirmatory Factor Analysis (CFA) and internal consistency using McDonald’s omega coefficient. Relying on the newest research we confirmed a five-factor structure for the CAS with the five factors being: Severe Combined Abuse, Sexual Abuse, Emotional Abuse, Physical Abuse, and Harassment. We also confirmed the three-factor structure for the SEA, resulting in Economic Control, Economic Exploitation, and Employment Sabotage. The instruments demonstrated high internal consistency. The validated instruments that measure multidimensionality of IPV will allow a more comprehensive data and knowledge collection of women’s experiences in abusive relationships.
Keywords: Composite Abuse Scale; Domestic violence; Scale of Economic Abuse; Lithuania; Battered women